IMPLEMENTASI ALGORITMA FP-GROWTH PADA PENEMPATAN PRODUK DI PRIMA DEWATA - Novem Berlian Uly; Murry Albert Agustin Lobo; Nyongki Daku Ali Hary; Yupiter Yiwa Hinggiranja (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
Effective product placement in a mini market or retail store is an important factor in increasing sales and customer satisfaction. The FP-Growth algorithm is able to identify patterns or relationships of products that are often purchased together, so that it can help in more strategic product arrangement. Prima Dewata faces challenges in optimizing product placement to attract customer attention and maximize available space. This study aims to identify patterns of product relationships that are often purchased together, so that related products can be strategically placed to attract consumer attention. This study begins with data collection, pre-processing, implementation of the FP-Growth Algorithm and analysis then results. The results obtained are that Sariwangi tea products are the most purchased products by Prima Dewata visitors in the period January - November 2024 and there are 4 main rules that can be used as a reference in compiling goods based on data processing results, namely 1. Sariwangi tea and Clear Men Shampoo (support: 0.682 and confidence: 0.867); 2. Sariwangi tea and Indomie Pepsodent Toothpaste (support: 0.171/ confidence: 0.876); 3. Sariwangi tea and Indomie Ayam Bawang (support: 0.175/ confidence: 0.922); 4. Sariwangi tea and Lifebuoy Soap (support: 0.166/ confidence: 0.937).